Composição florística, fitossociologia e influência dos solos na estrutura da vegetação em uma área de caatinga no semi-árido paraibano - Araújo, Lúcio Valério Coutinho de (2007)
In spite of the existence of works phytosociologys of the vegetation of the caatinga, still lack a lot for the knowledge of the caatingas as a completely. Consent exists among several authors in recognizing the heterogeneity floristic and physiognomies of the caatinga and in attributing to the climate and the soil, or still to the united action of these two factors, the main cause in the establishment of the caatinga types. The objective of the present work was to analyze the floristic composition, to compare the structure phytosociologycal, in the years of 2000 and 2005 and to evaluate the existent soil-vegetation relationship, the altitude and vegetable covering in one area caatinga in the farm Tamanduá, in the municipality of Santa Terezinha (PB), being adopted the method of plots, with 200m2 each, being made aleatory collections for 12 months. All shrub-trees vegetation with larger total height than 1 meter and circunference at breast height – CAP ³ 10 cm, alive or killed still foot, were counted and measured. Samples of surface soil (0-20 cm of depth) were collected from each plot for analyses of chemical and textural properties. Were defined three classes of altitudes with base in the estimates generated by interpolate: inferior, middleman and superior. Was sampling 1440 individuals, belonging to 25 species and 17 families, in the first rising, and 1704 individuals belonging to 27 species and 15 families, in the second rising. Caesalpinia pyramidalis was the most representative species in the two periods, what is due to the high values of density, dominance, frequency and distribution. The total basal area had a small increase between 2000 and 2005, passing of 10,73 m².ha-1 for 11,57 m².ha-1 an increment of 7,8 %. Of the individuals sampling, so much in the year of 2000 as in 2005, 92 % concentrated on the first four diameter classes, between 3 and 15 cm. Croton sonderianus Müll. Arg. presented the larger percentile of mortality. The number of individuals for hectare was of 1775. Of the found species, 67% can be considered as arborous and 33% as arbustive. Four families stopped about 54% of the individuals sampling: Euphorbiaceae, Caesalpinaceae, Mimosaceae and Bignoniaceae. The species that had the largest number of individuals sampling were: Caesalpinia pyramidalis Tul. (21,5%), Combretum leprosum Mart. (12,4%) and Croton sonderianus Müll. Arg. (8,5%). The species that more contributed with the inclusion of the new individual were: Combretum leprosum Mart., Croton sonderianus Müll. Arg., Caesalpinia pyramidalis Tul., Bauhinia cheilantha (Bong.) Stand. and Anadenanthera colubrine. The families that more stood in IVI were Caesalpiniaceae, Mimosaceae, Combretaceae and Euphorbiaceae, and Caesalpinia pyramidalis went to the species with larger density, being considered the three altitude levels. The chemical attributes of the soil, in the level of inferior altitude influenced in the individuals largest basal area and the chemical and physical attributes of the soil provided trees with larger IVI.